A life cycle assessment of ethanol produced from sugarcane molasses - Theka, Edward (Department of Chemical Engineering, 2014)
The environmental performance of production companies is increasingly becoming part of strategies for the competitive marketing of their products, as consumers grow more aware of environmental issues surrounding industry. Similar products can be compared by the tool of Life Cycle Assessment (LCA) from the perspective of their impacts on the environment from which their production resources are drawn and to which their burdens are released. There is the inherent perception that products made from renewable resources are environmentally more desirable than those which are produced from finite resources. This thesis investigates whether this conception is valid for the case of ethanol produced from biomass, by describing and interpreting the various stages of the production process by means of an LCA. Sugarcane (Saccharum o/ficinarum) contains 12 - 17% sugars on a wet basis, and 68 -72% moisture. The sugar composition is 90% sucrose and 10% glucose or fructose. In the conventional sugar production industry, syrup containing about 34% sucrose (molasses) remains after sugar crystals are formed from the clarified juice. This sucrose can be fermented to produce ethanol whose uses include potable consumption and the production of chemicals, but there is growing interest in its possible use as an additive for motor-grade gasoline, as well as its use as neat fuel to replace crude-oil based fuels. This thesis presents a cradle to gate life cycle study carried out with the aim of determining the environmental consequences of producing ethanol from sugarcane molasses. The investigation was done for a sugar producing company in the Kwa-Zulu Natal Province of South Africa, whose interests also lie in the beneficiation of value addition products from sugarcane. The goal of the study was to produce a comprehensive inventory of all the energy and material inputs and outputs involved in the production of the 1 kl (1000 litres) of bio-ethanol, using Life Cycle Assessment (LCA). Concepts of carbon closure and fossil energy ratio were chosen to represent measures of the degree of renewability of the system, and the results were compared to values derived from the literature on life cycle assessments of similar bioenergysystems.